2006
DOI: 10.1007/s00216-006-0623-y
|View full text |Cite|
|
Sign up to set email alerts
|

Development and characterization of an integrated silicon micro flow cytometer

Abstract: This paper describes an innovative integrated micro flow cytometer that presents a new arrangement for the excitation/detection system. The sample liquid, containing the fluorescent marked particles/cells under analysis, is hydrodynamically squeezed into a narrow stream by two sheath flows so that the particles/cells flow individually through a detection region. The detection of the particles/cells emitted fluorescence is carried out by using a collection fiber placed orthogonally to the flow. The device is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…It is also possible that several particles passed simultaneously. The achieved counting rates of this device compare well to other on‐chip cytometers, reporting counting rates of 0.4, 4–25, and <400 Hz [], respectively; in all cases, however, for larger particles. Even though both 2‐μm and 1‐μm particles could be detected separately, the large dispersion in peak height makes it, at the current state, unfeasible to perform measurements on solutions containing a mixture of both size particles.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…It is also possible that several particles passed simultaneously. The achieved counting rates of this device compare well to other on‐chip cytometers, reporting counting rates of 0.4, 4–25, and <400 Hz [], respectively; in all cases, however, for larger particles. Even though both 2‐μm and 1‐μm particles could be detected separately, the large dispersion in peak height makes it, at the current state, unfeasible to perform measurements on solutions containing a mixture of both size particles.…”
Section: Resultssupporting
confidence: 75%
“…Miniaturized flow cytometry using microfluidic principles provides an excellent detection platform with reduced sample consumption and represents an inexpensive alternative for bioparticle sizing and scattered light analysis []. Recently, with the help of microfabrication technology, flow cytometers have been miniaturized for bioparticle detection, or cell sorting and quantification based on various techniques []. Still, the most commonly used transduction signals in optical detection are fluorescence [].…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that particles down to 1 mm can be detected and counted reliably at 100 Hz for concentrations below 300 particles/mL. The achieved performance corresponds very well to other presented on-chip cytometers, with counting rates of 0.4, 4-25 and o400 Hz [14][15][16] respectively, though in all cases for much larger particles. It has been shown how the on-chip lenses can be used both for focusing the light directly at the point of detection and to couple light in and out of waveguides.…”
Section: Concluding Remarks and Outlooksupporting
confidence: 71%
“…This is due to the inherent obstacle faced by the field of microfluidics-effective on-chip miniaturization of all the components necessary for manipulation of fluids. External pressure-driven pumps often used in microflow cytometry applications include syringe pumps [7][8][9][10][11][12][13] and positively or negatively pressurized reservoirs using a compressed gas source or vacuum pump [14]. Passive pumping methods such as gravity-driven flow have also been used [15][16][17].…”
Section: Methods For Pumpingmentioning
confidence: 99%